Pengaruh Transformasi Digital Akuntansi dan Efektivitas Pengendalian Internal terhadap Kualitas Laporan Keuangan Perusahaan Jasa - nur haliza riang saputri; Suwarno (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the impact of digital transformation in accounting and the effectiveness of internal control systems on the quality of financial reports in an integrated logistics services company. The method used is a quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS), with data collected from 35 respondents who are involved in financial and accounting activities within the company. The analysis focuses on evaluating the relationships between digital transformation, internal control systems, and financial reporting quality. The research findings indicate that digital transformation in accounting (coefficient = 0.658; p-value = 0.000) and internal control systems (coefficient = 0.308; p-value = 0.023) have a positive and significant effect on the quality of financial reports. Furthermore, the coefficient of determination (R²) value of 0.822 shows that both independent variables are able to explain 82.2% of the variation in financial report quality, while the remaining percentage is influenced by other factors outside the model. These results confirm that the implementation of digital technology supported by an effective internal control system can significantly improve the accuracy, relevance, timeliness, and reliability of financial reporting in organizations.